Disease Mechanisms - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
Behcet syndrome (BS) is a systemic inflammatory disorder with a diverse spectrum of clinical manifestations including mucocutaneous, ocular, vascular, gastrointestinal, musculoskeletal, and central nervous system involvement [1]. A complex genetic background leading to a pro-inflammatory, innate immune system-derived activation perpetuated by adaptive immune responses against environmental antigens or/and autoantigens is accepted as the main pathogenic mechanism in BS [2, 3].
Keywords: REGULATORY T-CELLS; NATURAL-KILLER-CELLS; DAGGER-ETS DISEASE; FAMILIAL MEDITERRANEAN FEVER; MONOSODIUM URATE CRYSTALS; BLOOD MONONUCLEAR-CELLS; OCULAR BEHCETS-DISEASE; HEAT-SHOCK PROTEINS; PERIPHERAL-BLOOD; IMMUNE-RESPONSE